Phenotypic and Genotypic Characterization of Salmonella Typhi isolated from Human Blood with Distribution of Virulence Genes and Sequencing - Dola, Nigha Zannat; Shamsuzzaman, SM; Islam, Md Saiful; Rahman, Asma; Mishu, Nafisa Jabin; Nabonee, Modina Ansary; Jalil, Rafia Afreen (Community Based Medical Journal, 2023)
A cross-sectional study was conducted in the Department of Microbiology at tertiary care hospital in Bangladesh from July 2019 to June 2020, to see the phenotypic and genotypic characterization of Salmonella Typhi isolated from human blood with distribution of virulence genes and sequencing. Clinically suspected enteric fever patients irrespective of age and gender who attended either the Department of Microbiology or Medicine out-patient department (MOPD) in a tertiary level hospital in Bangladesh for blood culture and sensitivity test were included in this study. The positive growth S. Typhi was identified by gram straining, colony morphology and biochemical test. Then Salmonella Typhi was identified by using Salmonella specific antisera. Final identification was done by using 16s Rrna by PCR. Virulence factors like hemolysin and siderophore was detected by siderophores production assay. PCR and sequencing of virulence genes were done. A total number of 50 isolated organisms were identified as Salmonella species of which Salmonella Typhi was detected in 40 (48.2%) isolates. Among 40 isolated Salmonella Typhi, no Salmonella Typhi produced hemolysin and 30 (75.0%) isolates have ability to produce siderophore. Among the isolated Salmonella Typhi all isolates 40 (100%) were positive for viaB and staA gene, 21 (52.5%) were positive for iroB. Sequencing of viaB and iroB were done for further validation. In conclusion all isolated Salmonella Typhi carried viaB and staA, iroB genes were responsible for S. Typhi pathogenicity. CBMJ 2023 January: Vol. 12 No. 01 P: 41-47